Changes in concrete properties during pumping and formation of lubricating material under pressure. (June 2018) - Secrieru, Egor; Cotardo, Dario; Mechtcherine, Viktor; Lohaus, Ludger; Schröfl, Christof; Begemann, Christoph
Abstract: This study quantifies the changes in the rheological properties of fresh concrete while focusing on lubricating layer (LL) formation during pumping. Full-scale pumping experiments were carried out on ready-mix concrete accompanied by the state-of-the-art rheological tests. Pumping markedly increased the yield stress. It also led to an increase in the air content, which contributed to a decrease in viscosity of fresh concrete. The dynamic loading from pumping generates a pressure gradient in concrete over the pipe cross-section. The pressure gradient is assumed to facilitate the movement of lubricating material to the concrete-wall interface, completing the formation of LL. This postulate is based on experimental evidence obtained by a portable high-pressure filter press and the extracted filtrate. The amount of filtrate depends on the specific surface of the fines, on concrete bulk viscosity, and on chemical admixtures. Finally, an increase in concrete temperature was observed depending on the concrete's composition and the properties of the LL. Highlights: Pumping increases concrete yield stress and reduces its viscosity. Reduced viscosity is the result of increased air content in pumped fresh concrete. Pumping increases concrete temperature depending on concrete properties. The results of filtrate measurements correlate with the formation of the lubricating layer. The filtrate amount depends on the concrete viscosity and specific surface of fines.